Patient characteristics associated with a poor response to non-surgical multidisciplinary management of knee osteoarthritis: a multisite prospective longitudinal study in an advanced practice physiotherapist-led tertiary service. Issue 10 (6th October 2020) - O'Leary, Shaun; Raymer, Maree; Window, Peter; Swete Kelly, Patrick; Elwell, Bula; McLoughlin, Ian; O'Sullivan, Will; Phillips, Ben; Wake, Anneke; Ralph, Andrew; O'Gorman, Helen; Jang, Ellen; et al.
Abstract : Objectives: To explore patient characteristics recorded at the initial consultation associated with a poor response to non-surgical multidisciplinary management of knee osteoarthritis (KOA) in tertiary care. Design: Prospective multisite longitudinal study. Setting: Advanced practice physiotherapist-led multidisciplinary orthopaedic service within eight tertiary hospitals. Participants: 238 patients with KOA. Primary and secondary outcome measures: Standardised measures were recorded in all patients prior to them receiving non-surgical multidisciplinary management in a tertiary hospital service across multiple sites. These measures were examined for their relationship with a poor response to management 6 months after the initial consultation using a 15-point Global Rating of Change measure (poor response (scores −7 to +1)/positive response (scores+2 to+7)). Generalised linear models with binomial family and logit link were used to examine which patient characteristics yielded the strongest relationship with a poor response to management as estimated by the OR (95% CI). Results: Overall, 114 out of 238 (47.9%) participants recorded a poor response. The odds of a poor response decreased with higher patient expectations of benefit (OR 0.74 (0.63 to 0.87) per 1/10 point score increase) and higher self-reported knee function (OR 0.67 (0.51 to 0.89) per 10/100 point score increase) (p<0.01). The odds of a poor response increased with a greater degree of varus frontal knee alignment (OR 1.35 (1.03 to 1.78) per 5° increase in varus angle) and a severe (compared with mild) radiological rating of medial compartment degenerative change (OR 3.11 (1.04 to 9.3)) (p<0.05). Conclusions: These characteristics may need to be considered in patients presenting for non-surgical multidisciplinary management of KOA in tertiary care. Measurement of these patient characteristics may potentially better inform patient-centred management and flag the need for judicious monitoring of outcome for some patients to avoid unproductive care.